General conditions of phase cancellation in an acoustic field - VOGT, Michał (Archives of Acoustics, 1976)
The dependence of the degree of cancellation of an acoustic field, expressed by the field cancellation factor, on the correlation parameters of the signals: cancelling and cancelled is derived. Using this dependence, the necessary conditions — in terms of phase and amplitude — for the occurrence of the cancellation phenomenon at a field point are determined. The possibility of the cancellation of larger regions of acoustic fields is investigated using such parameters as spectral characteristics of various signal classes and mutual distances of the cancelling and cancelled sources. A classification into natural and forced cancellation is introduced and the classes of signals which can be cancelled in a natural way are determined. The conditions for the occurrence of cancellation throughout all space are determined.